2022
DOI: 10.1038/s41598-022-22175-3
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell populations differ in patients undergoing revision total knee arthroplasty for arthrofibrosis

Abstract: Arthrofibrosis following total knee arthroplasty (TKA) is a debilitating condition typically diagnosed based on clinical findings. To gain insight into the histopathologic immune cell microenvironment of arthrofibrosis, we assessed the extent of tissue fibrosis and quantified immune cell populations in specific tissue regions of the posterior capsule. We investigated specimens from three prospectively-collected, matched cohorts, grouped as patients receiving a primary TKA for osteoarthritis, revision TKA for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Recent researchers have illustrated that mononuclear phagocytes, especially activated M1 macrophages, are important in AF initiation and maintenance. 43 , 44 Clinical studies have demonstrated a positive correlation between M1 macrophage tissue density and preoperative patient-reported KSS outcomes. 44 In this study, we identified the M1-like F-Mφ subcluster as the key driver cell type of AF pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent researchers have illustrated that mononuclear phagocytes, especially activated M1 macrophages, are important in AF initiation and maintenance. 43 , 44 Clinical studies have demonstrated a positive correlation between M1 macrophage tissue density and preoperative patient-reported KSS outcomes. 44 In this study, we identified the M1-like F-Mφ subcluster as the key driver cell type of AF pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“… 43 , 44 Clinical studies have demonstrated a positive correlation between M1 macrophage tissue density and preoperative patient-reported KSS outcomes. 44 In this study, we identified the M1-like F-Mφ subcluster as the key driver cell type of AF pathogenesis. It is widely accepted that macrophages are not only permanent cells, that can transfer from M0 to M1/M2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune system–related biomarkers, including cytokines and immune cell populations, have also been investigated 92,98 . The innate 99 and adaptive 91,100 immune systems have been implicated in developing arthrofibrosis. In preliminary studies of arthrofibrosis biomarkers, patient cohorts have included those undergoing rTKA for arthrofibrosis compared with primary TKA patients with osteoarthritis and rTKA patients with nonfibrotic etiologies 48 .…”
Section: Diagnosismentioning
confidence: 99%
“…Salib et al found similar inflammatory marker profiles in the synovial fluid and serum of patients with and without arthrofibrosis 98 . Limberg et al showed that the fibrotic tissue and synovial fluid of patients with arthrofibrosis had decreased CD163+ macrophages and CD177+ mast cells, suggesting differential immune cell populations 99 . Seeking to characterize the adaptive immune response, Jenkins et al found increased levels of immunoglobulin (Ig) G1, IgG3, and anti-phosphatidyl serine IgG in the synovial fluid of patients with arthrofibrosis, from which they concluded that intra-articular interactions of T and B cells could be a source of immune complexes affecting scarring after TKA 100 .…”
Section: Pathophysiologymentioning
confidence: 99%